Leadership and Organizational Commitment Effects on Service Quality and Inpatient Satisfaction - Siti Masitoh; Rahayu Pudji Suci; Asih Tri Rachmi Nuswantari (Information Technology and Science (ITScience), 2026)
This study aims to analyze the effect of transformational leadership and organizational commitment on service quality and patient satisfaction, as well as to examine the mediating role of service quality. The research was conducted at Puskesmas Dedai, Sintang Regency, using a quantitative explanatory approach to explain causal relationships among the studied variables. The population consisted of 175 inpatients recorded over the last seven months, from which a sample of 64 respondents was selected using Slovin’s formula with a 10% margin of error through simple random sampling. Data were collected using structured questionnaires that measured transformational leadership, organizational commitment, service quality, and patient satisfaction. The collected data were analyzed using path analysis to examine both direct and indirect effects among variables. The results indicate that transformational leadership has a significant positive effect on service quality and patient satisfaction, which is reflected through leaders’ ability to provide role modeling, motivation, inspiration, and encouragement for innovation among employees. Organizational commitment also shows a significant direct effect on patient satisfaction, particularly through employees’ emotional attachment, loyalty, and moral responsibility toward the organization. Furthermore, service quality is proven to mediate the relationship between transformational leadership and patient satisfaction, indicating that effective leadership contributes to higher patient satisfaction primarily by improving service quality. However, service quality does not mediate the relationship between organizational commitment and patient satisfaction, suggesting that committed employees can directly influence patient satisfaction without necessarily improving perceived service quality. These findings emphasize the critical role of transformational leadership, organizational commitment, and service quality in enhancing patient satisfaction in public healthcare services.